2006
DOI: 10.1523/jneurosci.4508-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

GABA Regulates Dendritic Growth by Stabilizing Lamellipodia in Newly Generated Interneurons of the Olfactory Bulb

Abstract: The initial formation and growth of dendrites is a critical step leading to the integration of newly generated neurons into postnatal functional networks. However, the cellular mechanisms and extracellular signals regulating this process remain mostly unknown. By directly observing newborn neurons derived from the subventricular zone in culture as well as in olfactory bulb slices, we show that ambient GABA acting through GABA A receptors is essential for the temporal stability of lamellipodial protrusions in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 41 publications
4
74
0
Order By: Relevance
“…This increase in speed resulted in aberrant accumulation of neurons in the upper cortical layers. In the second study, Gascon et al (2006) showed that GABA regulates dendritic growth in cultured neuroblasts from the SVZ or in acute slices. In particular, bicuculline promoted the rapid stabilization of new dendritic segments.…”
Section: Gaba Signaling Molecules In the Svz And Rmsmentioning
confidence: 99%
“…This increase in speed resulted in aberrant accumulation of neurons in the upper cortical layers. In the second study, Gascon et al (2006) showed that GABA regulates dendritic growth in cultured neuroblasts from the SVZ or in acute slices. In particular, bicuculline promoted the rapid stabilization of new dendritic segments.…”
Section: Gaba Signaling Molecules In the Svz And Rmsmentioning
confidence: 99%
“…Previous studies identified several extracellular factors involved in the dendritogenesis of SVZ-derived OB interneurons, including GABA [58] and vascular endothelial growth factor (VEGF) [59]. Wnt5a, which likely activates the PCP signaling pathway, increases the neurite complexity of OB interneurons derived from the SVZ [35].…”
Section: Discussionmentioning
confidence: 99%
“…Depolarizing GABA signalling modulates dendritic development of postnatally generated neurons in both hippocampus and olfactory bulb (Gascon et al, 2006;Ge et al, 2007). In the OB, incubation of SVZ-derived cell cultures from postnatal rat (at 1 day in vitro; 1 DIV) as well as OB slices, with the GABA A receptor antagonist bicuculline (but not GABA B and GABA C receptors antagonists), shows a reduction in dendritic complexity affecting primarily the number and length of primary dendrites.…”
Section: Amino Acids: Gaba and Glutamatementioning
confidence: 99%
“…In the OB, incubation of SVZ-derived cell cultures from postnatal rat (at 1 day in vitro; 1 DIV) as well as OB slices, with the GABA A receptor antagonist bicuculline (but not GABA B and GABA C receptors antagonists), shows a reduction in dendritic complexity affecting primarily the number and length of primary dendrites. GABA application has an opposite effect stimulating dendritic growth in new neurons (Gascon et al, 2006). This effect of GABA on dendrites development affects only immature neurons and is mediated by GABA A receptor depolarization and calcium influx through L-type voltage gated calcium channels.…”
Section: Amino Acids: Gaba and Glutamatementioning
confidence: 99%
See 1 more Smart Citation